Causal effects of specific gut microbiota on musculoskeletal diseases: a bidirectional two-sample Mendelian randomization study - Chen, Shuai; Han, Huawei; Sun, Xiaohe; Zhou, Guowei; Zhou, Qing; Li, Zhiwei (Frontiers in Microbiology, 2023)
Recent observational studies and clinical trials demonstrated an association between gut microbiota and musculoskeletal (MSK) diseases. Nonetheless, whether the gut microbiota composition has a causal effect on the risk of MSK diseases remains unclear.Based on large-scale genome-wide association studies (GWAS), we performed a two-sample Mendelian randomization (MR) analysis to investigate the causal relationship between gut microbiota and six MSK diseases, namely osteoporosis (OP), fracture, sarcopenia, low back pain (LBP), rheumatoid arthritis (RA), and ankylosing spondylitis (AS). Instrumental variables for 211 gut microbiota taxa were obtained from the largest available GWAS meta-analysis (n = 18,340) conducted by the MiBioGen consortium. And the summary-level data for six MSK diseases were derived from published GWAS. The inverse-variance weighted (IVW) method was conducted as a primary analysis to estimate the causal effect, and the robustness of the results was tested via sensitivity analyses using multiple methods. The Bonferroni-corrected test was used to determine the strength of the causal relationship between gut microbiota and various MSK diseases. Finally, a reverse MR analysis was applied to evaluate reverse causality.According to the IVW method, we found 57 suggestive causal relationships and 3 significant causal relationships between gut microbiota and MSK diseases. Among them, Genus Bifidobacterium (β: 0.035, 95% CI: 0.013 -0.058, P = 0.0002) was associated with increased left handgrip strength, Genus Oxalobacter (OR: 1.151, 95% CI: 1.065 -1.245, P = 0.0003) was correlated with an increased risk of LBP, and Family Oxalobacteraceae (OR: 0.792, 95% CI: 0.698-0.899, P = 0.0003) was linked with a decreased risk of RA. Subsequently, sensitivity analyses revealed no heterogeneity, directional pleiotropy, or outliers for the causal effect of specific gut microbiota on MSK diseases (P > 0.05). Reverse MR analysis showed fracture may result in a higher abundance of Family Bacteroidales (P = 0.030) and sarcopenia may lead to higher abundance of Genus Sellimonas (P = 0.032).Genetic evidence suggested a causal relationship between specific bacteria taxa and six MSK diseases, which highlights the association of the "gut-bone/muscle" axis.Further exploration of the potential microbiota-related mechanisms of bone and muscle metabolism might provide novel insights into the prevention and treatment of MSK diseases.